2020
DOI: 10.3389/fmars.2020.530757
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Carbonate Shell of Emiliania huxleyi Provides Limited Protection Against Viral Infection

Abstract: Coccolithophores are an important group of marine phytoplankton which cover themselves with the coccosphere -a shell composed of numerous calcium carbonate (CaCO 3 ) platelets. Despite more than a century of coccolithophore research, it remains speculative why coccolithophores calcify. Resolving this question is essential to assess the competitive fitness of coccolithophores in the future ocean where changes in calcification are expected. Here, we used the Emiliania huxleyi -Emiliania huxleyi Virus 86 host-vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…It is worth noting that while we used a commonly studied non-calcified E. huxleyi strain (e.g., Bidle et al, 2007 ; Evans et al, 2007 ; Johns et al, 2019 ; Gilg et al, 2016 ; Pasulka et al, 2018 ; Goode et al, 2019 ; Knowles et al, 2020 ), we expect the results from this study are also representative of infection of calcified strains. The infection dynamics and virion production are not significantly impacted by whether the host cells are calcified or not ( Paasche, 2001 ; Haunost et al, 2020 ). However, variations in strains of hosts and virions and host physiology more likely account for reported differences in infection success and dynamics ( Allen et al, 2007 ; Kegel et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that while we used a commonly studied non-calcified E. huxleyi strain (e.g., Bidle et al, 2007 ; Evans et al, 2007 ; Johns et al, 2019 ; Gilg et al, 2016 ; Pasulka et al, 2018 ; Goode et al, 2019 ; Knowles et al, 2020 ), we expect the results from this study are also representative of infection of calcified strains. The infection dynamics and virion production are not significantly impacted by whether the host cells are calcified or not ( Paasche, 2001 ; Haunost et al, 2020 ). However, variations in strains of hosts and virions and host physiology more likely account for reported differences in infection success and dynamics ( Allen et al, 2007 ; Kegel et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lightly calcified A morphotype was rare and did not show any clear pattern in its distribution. The A-CC morphotype has been associated with coastal upwelling zones in the Atlantic (Giraudeau et al, 1993;Smith et al, 2012;Henderiks et al, 2012) but not reported from the 7-18 33.4-35.6 Poulton et al (20117-18 33.4-35.6 Poulton et al ( , 2013 a E. huxleyi as a component of larger coccolithophore assemblages. When information about other coccolithophores was provided, the percentage abundance of E. huxleyi is given or if it was noted that E. huxleyi was dominant.…”
Section: Comparison Of E Huxleyi Morphotypes In Patagonia To Nearby Oceans and Norwegian Fjordsmentioning
confidence: 95%
“…Cells were decalcified prior to experiments using an established low-pH decalcification protocol. 25 A Beckman Coulter Z2 with a 100 μm orifice was used to collect cell count and median cell size as described by Fan et al 22 Decalcified cells were measured in bulk at 0 h, then aliquoted into a well plate prior to treating with 10 μΜ CPP-PNA. Throughout the incubation process, the cells were maintain in standard L1-Si/25 media.…”
Section: Cellular Uptake Of Cpp-fitc and Cpp-pna-fitcmentioning
confidence: 99%